Development of an immunological technique for detecting granulovirus infection in Tuta absoluta larvae (Lepidoptera: Gelechiidae) (2012)
Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae), known as tomato moth or tomato leafminer is a microlepidopter from Gelechiidae’s family, which is widely distributed on America, Europe, Africa and Asia and is considered the most important pest of this crop (Roditakis et al. 2010). Phthorimaea operculella granulovirus (PhopGV) has been used for controlling larvae of different moths from Gelechiidae’s family as Tecia solanivora and P. operculella in several countries of South America as Colombia, Brazil, Argentina and Peru, and probably can also be pathogenic for T. absoluta larvae. However, viral isolates from this insect has not been reported nowadays, possibly due to the small larvae size and the difficulty for detecting the virus. In this sense, the aim of the present work was to develop an economic, fast and accurate immunological technique for granulovirus detection in T. absoluta larvae